Novel insights into the N 6-methyladenosine modification on circRNA in cancer - Xu, Qingling; Jia, Yi; Liu, Ying; Wu, Bing; Wang, Jianxun; Ao, Xiang; Ding, Wei (Frontiers in Oncology, 2025)
Circular RNAs (circRNAs) are a class of non-coding RNAs (ncRNAs) generated through the reverse splicing of mRNA precursors (pre-mRNAs). They possess a unique loop structure and exhibit remarkable stability. CircRNAs have emerged as promising biomarkers for cancer, with specific circRNAs playing crucial roles in cancer drug discovery, treatment, and resistance mechanisms. N6 methyl adenosine (m6A) represents the most prevalent RNA modification in eukaryotes. In 2017, researchers identified that m6A modifications also occur in circRNAs, displaying unique characteristics. m6A-modified circRNAs undergo reversible regulation mediated by enzymes involved in m6A modification pathways. These modified circRNAs interact with m6A-binding proteins, thereby influencing processes such as alternative splicing, translation and degradation. Some circRNAs enhance their metabolism or facilitate nuclear export to the cytoplasm by interacting with enzymes involved in m6A regulation. The study of m6A-modified circRNAs has gained great attention in circRNA research due to their association with various diseases. This review summarizes the functional mechanisms of circRNAs regulated by m6A modifications and their implications in cancer occurrence and therapy, with a primary focus on the genesis, regulatory mechanisms, and functional roles of m6A-modified circRNAs in the biology of diverse types of cancers. Additionally, we explore the potential application of m6A-modified circRNAs in clinical cancer treatment.